Comment on "Structural, electrical, and multiferroic characteristics of lead-free multiferroic: Bi(Co0.5Ti0.5)O3–BiFeO3 solid solution" by N. Kumar, A. Shukla, N. Kumar, R. Choudhary and A. Kumar, RSC Adv., 2018, 8, 36939". Issue 46 (20th October 2022) - Tomaszewski, Paweł E.
Abstract : The significant errors in the crystallographic part of the commented paper are described. The new chemical formula of the studied crystal is proposed: Bi25 FeO39 : Co, Ti. The coexistence of two sillenite type phases is evidenced. Abstract : My comments concern the significant errors in the crystallographic part of the commented paper. It was found that the studied crystal is of the sillenite type and the correct formula should be Bi25 FeO39 : Co, Ti instead of BiFeO3 . Moreover, the type of unit cell is not correct. Due to the double doping the new type of unit cell, previously unknown, was proposed for such crystals. Furthermore, the authors did not find that the studied sample contains two slightly different phases, both of the sillenite type. The actual chemical composition of the studied crystals is not known.